FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PERTUMBUHAN PADA BALITA SUKU BANJAR DI PUSKESMAS SUNGAI SALAK - Suryani Suryani; Oswati Hasanah; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Growth is an indicator of the health status of children. The factors that affect sosio-economic are education, occupation, income, and number of family dependents. The purpose of this study was to determine the socioeconomic factors that affect the growth of toddlers in the Banjar tribal in Tempuling, Indragiri Hilir District. The design of this study was descriptive correlation with cross sectional approach. Sample of this study was 130 respondents using total sampling techniques. The measuring instrument used was a questionnaire. The analysis used was univariate and bivariate analysis with chi square test and the alternative kolmogorov smirnov test with α = 0.05. The results showed that mothers of children under five years were 26-35 years (56.5%), all respondents were moslem (100%), age of the toddlers were 13-36 months (66.9%), majority of toddlers were male (56.2%), majority of respondents were low education (70%), occupation of head of families were in informal sector (60.8%), the income was under the minimum wage (72,3%), number of family dependents were 1-3 families (75.4%), toddlers growth status based on TB/U at normal category (67.7%) and based on BB/U at normal category (61.5%). Bivariate analysis show that there is a significant correlation between occupation and income with toddlers growth (TB/U), but there is no correlation between education, occupation, and number of family dependents with toddlers growth (BB/U).Keywords: growth,social-economic factors,toddlers